Enhance the Efficiency of the Regenerative Braking System in Electric Vehicles using a Hybrid Energy Storage System - bin Zulkarnian Gafoor, Muhammad Naseem Azlan; AHMED SADEQ, TAHA MOHAMMED (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Electric vehicles (EVs) are poised to revolutionise urban transportationby offering reduced emissions, enhanced energy efficiency, and sustainable transportation solutions compared to conventional internal combustion engine vehicles. A key factor in their efficiency is regenerative braking systems, which capture and convert kinetic energy into electrical energy during deceleration. However, challenges such as limited energy recovery efficiency and battery lifespan remain significant barriers. This paper proposes a novel approach to address these challenges through the development and simulation of a Battery-Supercapacitor Hybrid Energy Storage System (HESS) tailored for EVs. The study uses MATLAB/Simulink simulations and evaluates the system's performance under various standard drive cycles (Urban Dynamometer Driving Schedule - UDDS, New York City Cycle - NYCC, and New European Driving Cycle - NEDC). By integrating supercapacitors alongside batteries, the HESS aims to enhance regenerative braking efficiency, prolong battery life, and optimize energy utilization. The findings highlight that the integration of supercapacitors with batteries in the HESS significantly improves energy recovery during braking events, especially in urban stop-and-go driving conditions represented by the selected drive cycles. This enhancement not only increases overall vehicle efficiency but also reduces stress on the battery, thereby extending its operational lifespan. In conclusion, the study suggests that strategic energy management through HESS offers promising avenues for advancing EV technology and contributing to sustainable mobility solutions in urban environments.